Policy optimization for high-quality development and openness of China's healthcare sector: a tripartite evolutionary game based on wholly foreign-owned hospitals, public hospitals and the government - Xiao, Liu; Qingjin, Wang; Hao, Gao; Shan, Jiang (Frontiers in Public Health, 2025)
IntroductionWith the intensification of population aging and the diversification of medical demands, China's healthcare system faces dual challenges of ensuring public welfare and improving efficiency. To enhance China's medical service capabilities, upgrade medical technologies, and expand diversified service supply patterns, the Chinese government has permitted the establishment of wholly foreign-owned hospitals.MethodsThis study constructs a tripartite evolutionary game model involving wholly foreign-owned hospitals, public hospitals, and the government, combined with system dynamics simulation, to explore policy optimization pathways for high-quality development and sustained opening-up in China's healthcare industry.Results and discussionThe entry decisions of wholly foreign-owned hospitals are driven by economic returns and policy support, where government subsidies can accelerate their entry into the Chinese market but exhibit diminishing marginal utility. The transformation of public hospitals is primarily influenced by government financial subsidies, with subsidy intensity exhibiting a positive correlation with the degree of transformation; however, high subsidies are unsustainable. Government regulatory strategies are constrained by both social losses and regulatory costs, which require balancing short-term interventions with long-term sustainability. Based on these findings, this study argues that China's healthcare industry should continuously improve the regulations on foreign investment access, allow social funds to enter the healthcare industry, establish comprehensive urban medical alliances, and refine the regulatory measures, among others.